2020
DOI: 10.3390/cancers12113311
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in Sigmoid Colon Cancer: A Search for Potential Biomarkers

Abstract: The aberrant expression of microRNAs in known to play a crucial role in carcinogenesis. Here, we evaluated the miRNA expression profile of sigmoid colon cancer (SCC) compared to adjacent-to-tumor (ADJ) and sigmoid colon healthy (SCH) tissues obtained from colon biopsy extracted from Brazilian patients. Comparisons were performed between each group separately, considering as significant p-values < 0.05 and |Log2(Fold-Change)| > 2. We found 20 differentially expressed miRNAs (DEmiRNAs) in all comparisons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…For example, miR-144 was reported to target KLF4 to increase the proliferation and invasion of CRC stem cells (31). Marques et al (32) analyzed the differentially expressed genes in tissue samples of patients with CRC from the TCGA database and identified several potential novel biomarkers, such as hsa-miR-125b-2-3p, hsa-miR-1248 and hsa-miR-190a-5p. The present study demonstrated that miR-146b-5p expression was significantly increased in CRC tissue and cells compared with normal tissue and cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-144 was reported to target KLF4 to increase the proliferation and invasion of CRC stem cells (31). Marques et al (32) analyzed the differentially expressed genes in tissue samples of patients with CRC from the TCGA database and identified several potential novel biomarkers, such as hsa-miR-125b-2-3p, hsa-miR-1248 and hsa-miR-190a-5p. The present study demonstrated that miR-146b-5p expression was significantly increased in CRC tissue and cells compared with normal tissue and cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another recent study evaluated the role of microRNA to search for prognostic biomarkers associated with sigmoid CC. 6 Human leukocyte antigen (HLA) class II molecule has been reported as a prognostic biomarker for many cancers including gastric cancer, 7 and colorectal cancer (CRC). 8,9 However, until now few studies have examined the polymorphism of HLA class II as a biomarker for LCC and RCC in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…5 Another recent study evaluated the role of microRNA to search for prognostic biomarkers associated with sigmoid CC. 6…”
Section: Introductionmentioning
confidence: 99%